STRUCTURAL AND CATALYTIC FEATURES AFFECTING INACTIVATION OF TYPICAL 2-CYS HUMAN PEROXIREDOXINS 2 AND 3 - Haynes, Alexina (Wake Forest University, 2013)
Reactive oxygen species are key mediators of intracellular signaling and significantly influence the progression of several pathophysiologies. Oxidative stress damages macromolecules (lipids, nucleic acids and proteins). Antioxidant enzymes play a critical homeostatic role in modulating the survival and death signaling pathways in the cells of the complex interconnected systems within the human body. One such class of enzymes, human typical 2-cys peroxiredoxins, is involved in redox regulation through the cyclic oxidation and reduction of cysteine residues during its normal catalytic cycle. This redox cycling facilitates hydrogen peroxide (H2O2) based cell signaling, protects cells from oxidative stress and inhibits apoptosis. There are four members of this class with disparate subcellular distributions: Prx1, Prx2 (both in the cytoplasm), Prx3 (mitochondria) and Prx4 (endoplasmic reticulum). They possess an evolutionary adaptation within the C-terminus that allows these `sensitive' Prxs to be susceptible to hyperoxidation. Under normal conditions this allows the propagation of localized H2O2 signaling (`Floodgate Hypothesis') and resumption of peroxidase activity when the hyperoxidized Prx is repaired by sulfiredoxin (Srx). However, during extreme oxidative stress, antioxidant defense mechanisms fail, resulting in damage to several organs, such as the myocardium, liver, ovaries, pancreas and brain, leading to cardiomyopathy, cancer, metabolic disorders and neurodegenerative diseases.
Keywords: Homology modeling; Hyperoxidation; Peroxiredoxin; Sulfenamide; Sulfiredoxin; X-ray crystallography